Efforts to Optimize the Office of Religious Affairs of Paleleh District Buol Regency in overcoming the increase in early marriage after the Covid-19 pandemic - Risky Yanto Yunde; Nur Mohamad Kasim; Dolot Alhasni Bakung (Estudiante Law Journal, 2023)
Early marriage experienced by adolescents under 19 years old is still a phenomenon in several regions in Indonesia. Early marriage is more likely to occur in any Religion Paleleh sub-district, Buol Regency is one of the sub-districts where the number of cases of early marriage is quite high and has increased after the co-19 pandemic. This needs to be prevented by all actions, activities, or efforts carried out by the Regional Government, community, family, and parents as well as all stakeholders to reduce the rate of early marriage. The purpose of conducting this research is to find out the efforts of the Religious Affairs Office of Paleleh District, Buol Regency in overcoming the increase in early marriage after the Covid-19 pandemic. Using a sociological juridical research method, using a descriptive qualitative research approach and interactive analysis techniques. The results of the research conducted stem from the responses of various elements of the Paleleh District community regarding early marriage, which contain a lot of speculation, namely positive and negative responses. Responses from rural communities where people are still less aware and less compliant with the law. Early or underage marriages that still occur are often due to factors caused by the social model of young people who are too free with the opposite sex. However, it is all returned to the parents. For the people of Paleleh Subdistrict who have low economic constraints who cannot afford to send their children to school, especially for women, supported by the negative stigma factor that there is no point in going to high school and the kitchen will be the place to return to.